The effects of oral glutamine supplementation on athletes after prolonged, exhaustive exercise - Castell, L. M.; Newsholme, E. A. (Nutrition, 1997)
Athletes undergoing intense, prolonged training or participating in endurance races suffer an increased risk of infection due to apparent immunosuppression. Glutamine is an important fuel for some cells of the immune system and may have specific immunostimulatory effects. The plasma glutamine concentration is lower after prolonged, exhaustive exercise: this may contribute to impairment of the immune system at a time when the athlete may be exposed to opportunistic infections. The effects of feeding glutamine was investigated both at rest in sedentary controls and after exhaustive exercise in middle-distance, marathon and ultra-marathon runners, and elite rowers, in training and competition. Questionnaires established the incidence of infection for 7 d after exercise: infection levels were highest in marathon and ultra-marathon runners, and in elite male rowers after intensive training. Plasma glutamine levels were decreased by approximately 20% 1 h after marathon running. A marked increase in numbers of white blood cells occurred immediately after exhaustive exercise, followed by a decrease in the numbers of lymphocytes. The provision of oral glutamine after exercise appeared to have a beneficial effect on the level of subsequent infections. In addition, the ratio of T-helper/T-suppressor cells appeared to be increased in samples from those who received glutamine, compared with placebo.